Innovation in Technology Management. The Key to Global Leadership. PICMET '97
DOI: 10.1109/picmet.1997.653557
|View full text |Cite
|
Sign up to set email alerts
|

Assembly planning in a virtual environment

Abstract: This paper presents novel tools to assist manual assembly in an virtual environment. While assembling virtual components, the user's actions are logged and an assembly plan is produced. Prototyping is reduced and concurrency is enhanced using such tools. Successful pilot studies have now been completed.Index terms -virtual reality, assembly planning, manual assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…The review in the previous section indicated that initial efforts in simulating assembly used pre-defined transformation matrices of parts for positioning in the virtual scene. In such systems, as users moved parts in the environment they were snapped in place based on collision or proximity criteria [122] (Figure 9). Most of the early applications did not implement collision detection among objects which allowed them to interpenetrate during the simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review in the previous section indicated that initial efforts in simulating assembly used pre-defined transformation matrices of parts for positioning in the virtual scene. In such systems, as users moved parts in the environment they were snapped in place based on collision or proximity criteria [122] (Figure 9). Most of the early applications did not implement collision detection among objects which allowed them to interpenetrate during the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving the human aspect out of the assembly planning could result in incorrect or inefficient operations. Another limitation of the computer aided assembly planning methods is that as the number of parts in the assembly increase, the possible assembly sequences increase exponentially and thus it becomes more difficult to characterize criteria for choosing the most suitable assembly sequence for a given product [17].…”
Section: Why Virtual Assembly?mentioning
confidence: 99%
“…The immersive VR assembly research system developed for this research (Dewar 1998) was based on a hardware platform comprising a Hewlett-Packard 725/75 workstation incorporating the HP-UX 10.01 operating system with a graphics accelerator for driving a head mounted display (HMD) and a 3D mouse. User HMD and 3D mouse tracking was carried out via a Polhemus tracker.…”
Section: Virtual Assembly Planningmentioning
confidence: 99%
“…The immersive VR systems offered an intuitive, unrestrained, real-time means of interaction which helped highlight clashes and inconsistencies in assemblies which cannot be easily be seen with a conventional, flat-screen CAD interface. The structure of the UVAVU (Unbelievable Vehicle for Assembling Virtual Units) assembly system is shown in figure 1 and utilized both proximity and collision snapping (Dewar et al 1997a, Dewar et al 1997b due to the lack of haptic feedback and more elaborate visual cues. Figure 1 The UVAVU assembly system.…”
Section: Virtual Assembly Planningmentioning
confidence: 99%
“…Dewar et al [7] indicated that in the process of product assembly, since it always involved such problems as product design and assembly, it had to rely on professional knowledge and the actual assembly by experienced experts so as to formulate standard assembly procedures. Therefore, in order to decrease effectively the time spent on the assembly procedures of product, VR technology is up to now a technology most frequently applied.…”
Section: Introductionmentioning
confidence: 99%